2004
DOI: 10.1079/bjn20041265
|View full text |Cite
|
Sign up to set email alerts
|

Apical sodium–glucose co-transport can be regulated by blood-borne glucose in the ruminal epithelium of sheep (Ovis aries, Merino breed)

Abstract: The intestinal Na-dependent D-glucose co-transporter (SGLT)-1 in sheep is under dietary regulation by luminal substrates. The aim of the present study was to find out whether the SGLT-1 in the forestomach of sheep is also regulated by sugars. Furthermore, the location of a possible glucosensor (luminal v. intracellular v. basolateral) was to be elucidated. Ruminal epithelia of sheep (Ovis aries, Merino breed) were pre-incubated in Ussing chambers with various substrates on the mucosal (i.e. luminal) or serosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This is remarkable and supports the functional relevance of a previously postulated sugar-sensing mechanism on the basolateral side of ruminal epithelia. An earlier study had shown that serosal pre-incubation with D -glucose, D -mannose, 3-O-methyl- D -glucose or sucrose can up-regulate apical glucose uptake of isolated ruminal epithelia via such sensor [60]. It was speculated in that previous publication that the functional relevance of this mechanism is to adapt ruminal glucose absorption to the supply of easily fermentable carbohydrates, especially sugars, to the rumen because increased sugar supply to the rumen can effectively trigger an increase in blood glucose [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is remarkable and supports the functional relevance of a previously postulated sugar-sensing mechanism on the basolateral side of ruminal epithelia. An earlier study had shown that serosal pre-incubation with D -glucose, D -mannose, 3-O-methyl- D -glucose or sucrose can up-regulate apical glucose uptake of isolated ruminal epithelia via such sensor [60]. It was speculated in that previous publication that the functional relevance of this mechanism is to adapt ruminal glucose absorption to the supply of easily fermentable carbohydrates, especially sugars, to the rumen because increased sugar supply to the rumen can effectively trigger an increase in blood glucose [60].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study had shown that serosal pre-incubation with D -glucose, D -mannose, 3-O-methyl- D -glucose or sucrose can up-regulate apical glucose uptake of isolated ruminal epithelia via such sensor [60]. It was speculated in that previous publication that the functional relevance of this mechanism is to adapt ruminal glucose absorption to the supply of easily fermentable carbohydrates, especially sugars, to the rumen because increased sugar supply to the rumen can effectively trigger an increase in blood glucose [60]. This is different from the intestine of sheep where upregulation of glucose absorption is also triggered by an increased supply of sugars but the sensor is luminal [6163].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SGLT1 expression was upregulated in the ileum of the Met‐Met group than the Met group, which was consistent with different blood glucose levels in these two groups. It may be resulted from higher blood glucose level in the Met‐Met group via an extracellular sugar‐sensing mechanism (Atasoglu, Gäbel, & Aschenbach, ).…”
Section: Discussionmentioning
confidence: 99%
“…Short‐term influences are due to activation or inactivation of transport proteins whereas long‐term influences are due to changes of mRNA‐expression, i.e., by influencing the transcription process. Concerning rapid changes, Atasoglu et al. (2004) have shown that the ovine SGLT1 can be stimulated by glucose and other substrates within minutes.…”
Section: The Story About Glucosementioning
confidence: 99%